Halal entertainment: Attraction of three-star hotel towards alternatives entertainment - Hashim, Khairusy Syakirin Has-Yun; Mat Daud, Zainab Aqilah; Jamaludin, Mohd Aizat; Mahamod, Lukman Hakim; Ahmad Fadzillah, Nurrulhidayah; Othman, Rashidi (2016)
Hotel ratings are used to classify hotels according to their quality. The objectives of hotel rating is to focus on the hotel experience as a whole. Three-star hotels and above attract their guest by providing various types of services and facilities. Hotels are independently assessed in traditional systems and rest heavily on the facilities provided. This standard make discrimination to some people those have lower budget to experience certain services. In fact two-star hotels can provide certain facilities like entertainment in different ways to give more services and attract more people. This paper critically discussed from Islamic perspective or also known as halal entertainment on the implementation of light entertainment services existing in two-star hotels to attract guests. Interviews and observation has been used to analyse the implementation of entertainments in the two-star hotels. This study demonstrated that most two-star hotels provide very little entertainments due to some limitations. As a conclusion, two-star hotels can also provide more entertainments that shariah compliant to attract guests besides in limited spaces and financial constraint.